Peran Otoritas Jasa Keuangan dalam Pengawasan Lembaga Baitul Maal wa Tamwil (BMT): Studi Kasus BMT Global Insani - Tita Novitasari (Fakultas Hukum Universitas Jambi, 2019)
This article discusses the role and involvement of the Financial Services Authority (OJK) in overseeing the Baitul Maal wa Tamwil (BMT) institution, especially in relation to the protection of illegal BMT customers. After the legislation and enactment of Law Number 1 of 2013 about Microfinance Institutions (UULKM), the establishment, guidance, regulation, and supervision of BMTs have changed. BMT organizations that originally could have been in the form of cooperative, foundation, limited liability companie, and even non-governmental organization, now must be in the form of cooperative or limited liability companie. However, in terms of guidance, OJK still needs to coordinate with ministries that carry out cooperative and domestic affairs, and therefore LKM guidance are actually under three authorities: OJK, the Ministry of Cooperatives and SMEs, and the Ministry of Home Affairs. Whereas in terms of regulation and supervision, authority is absolutely in OJK. The validity of UULKM also requires BMT to obtain a business license from OJK, and if not, the status means illegal. Taking the BMT (illegal) Global Insani case as an example, this article shows the role of OJK in BMT supervision has been expanded, from the institutional to the consumer protection aspects. Consumer protection efforts that can be done by OJK are through the mechanism of complaint, investigation, reporting, and prosecution. Abstrak Artikel ini membahas peran dan keterlibatan Otoritas Jasa Keuangan (OJK) dalam mengawasi lembaga Baitul Maal wa Tamwil (BMT), terutama dikaitkan dengan perlindungan nasabah BMT ilegal. Pasca dibentuk dan diberlakukannya Undang-undang Nomor 1 Tahun 2013 tentang Lembaga Keuangan Mikro (UULKM), maka pendirian, pembinaan, pengaturan, dan pengawasan BMT menjadi berubah. Organisasi BMT yang semula dapat berupa koperasi, yayasan, perseroan terbatas, dan bahkan kelompok swadaya masyarakat, saat ini harus berbentuk koperasi atau perseroan terbatas. Namun demikian, dalam hal pembinaan, OJK masih perlu berkoordinasi dengan kementerian yang menyelenggerakan urusan koperasi dan dalam negeri, dan karenanya LKM sesungguhnya berada di bawah tiga otoritas, yaitu OJK, Kementerian Koperasi dan UKM, dan Kementerian Dalam Negeri. Sedangkan dalam hal pengaturan dan pengawasan, kewenangan secara absolut ada pada OJK yang. Keberlakuan UULKM juga mewajibkan BMT memperoleh izin usaha dari OJK, dan jika tidak, statusnya berarti ilegal. Dalam artikel ini ditunjukkan, dengan mengambil contoh BMT (ilegal) Global Insani, peran OJK dalam pengawasan BMT telah diperluas, dari aspek kelembagaan hingga aspek perlindungan konsumen. Perlindungan konsumen yang dapat dilakukan OJK ialah melalui mekanisme pengaduan, penyelidikan, hingga pelaporan dan penuntutan.